Sex Differences in Outcomes After STEMI: Effect Modification by Treatment Strategy and Age - Cenko, Edina; Yoon, Jinsung; Kedev, Sasko; Stankovic, Goran; Vasiljevic, Zorana; Krljanac, Gordana; Kalpak, Oliver; Ricci, Beatrice; Milicic, Davor; Manfrini, Olivia; van der Schaar, Mihaela; Badimon, Lina; et al. (American Medical Association (AMA), 2018)
Previous works have shown that women hospitalized with ST-segment elevation myocardial infarction (STEMI) have higher short-term mortality rates than men. However, it is unclear if these differences persist among patients undergoing contemporary primary percutaneous coronary intervention (PCI).